Peran Badan Usaha Milik Desa dalam Mengembangkan Usaha Kecil di Desa Pelajau Kecamatan Banyuasin III Kabupaten Banyuasin - Rozi Rozi; Maulana Maulana; Alamsyah Alamsyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Rozi.This study aims to describe the role of village-owned enterprises in developing small businesses in Pelajau Village, Banyuasin III District, Banyuasin Regency. This research was conducted for three months using a descriptive qualitative approach. Data was collected through interviews, observation, and documentation. Data analysis techniques were carried out by presenting data, reducing data, and drawing conclusions. The results of the study indicate that the establishment of a Village-Owned Enterprise has the aim of improving the village economy, optimizing village assets so that they are useful for village welfare, increasing community efforts in managing the village's economic potential through SMEs In this case Pelajau Village Owned Enterprises have human resources that are quite good and facilities that are quite supportive, it's just how the implementation process will determine the success of each program to be implemented. With the existence of sufficient human resources and supported by village facilities and infrastructure, it is expected to be able to explore the economic potential of pelajau villages through BUMDes. With the commitment and quality of BUMDes management in collaboration with the community, of course, the hope to build the needed job opportunities will be realized through the development of village potential and creative economic activities in Pelajau Village. The implementation of the Village-Owned Enterprise program also involves other parties, namely other community institutions, especially those in Pelajau Village and organizations that are included in the activities of Village-Owned Enterprises and the community in general.